2021
DOI: 10.1155/2021/9920270
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Intake and Barriers to Their Consumption among University Students in Kuwait: A Cross-Sectional Survey

Abstract: Data on fruit and vegetable (F/V) consumption and barriers to their intake by Kuwait college students are needed for health promotional activities to curtail obesity and related comorbidities prevalent in Kuwait. This study employed a cross-sectional survey aimed at assessing the median F/V intake in a sample of Kuwait University students to determine its relationship with gender, body weight, college affiliation, and family monthly income and to explore perceived barriers to eating F/V. The median total F/V i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…Keim, Stewart, and Voichick in 1997 noted that, even though most youths are aware of the need to take fruits and vegetables, majority lack clarity regarding the health benefits of the practice, especially on daily doses [14]. The study by Alkazemi and Salmean in 2021 also supports the lack of awareness among students by analyzing a focus group of Kuwait Students [15]. The authors insist that a lack of clarity regarding F/V intake proportions for assessing and managing different functions makes it challenging for the group to maintain consistency in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Keim, Stewart, and Voichick in 1997 noted that, even though most youths are aware of the need to take fruits and vegetables, majority lack clarity regarding the health benefits of the practice, especially on daily doses [14]. The study by Alkazemi and Salmean in 2021 also supports the lack of awareness among students by analyzing a focus group of Kuwait Students [15]. The authors insist that a lack of clarity regarding F/V intake proportions for assessing and managing different functions makes it challenging for the group to maintain consistency in practice.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Kuwaiti university students were surveyed regarding their consumption of fruits and vegetables. Analysis of the results revealed that consumption was low due to certain barriers like lack of awareness of benefits, the temptation of tastier processed foods, the short shelf life of fruits and vegetables, and time-consuming preparations ( 31 ) . Thus, the importance of educating families on healthy eating habits is a necessity.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is expected that plant-based dieters have a high intake of these food groups, it has been reported that in general, college students do not consume them as they should and in fact, the vast majority of college aged individuals fail to meet the 5 a day intake recommendation (Schroeter and House, 2015;Rodrigues et al, 2019). Alkazemi and Salmean (2021) state that this is due to taste, inconvenience and lack of knowledge on F/V intake recommendations and preparation methods (Alkazemi and Salmean, 2021) while Schroeter and House (2015) include a rising demand for fast, convenient foods and declining cooking skills to the list of intake barriers in this age group (Schroeter and House, 2015).…”
Section: Discussionmentioning
confidence: 99%